2013
DOI: 10.1177/1038416213478805
|View full text |Cite
|
Sign up to set email alerts
|

Supervision in the helping professions: Making the case for support and supervision for career counsellors

Abstract: The case for supervision for career counsellors has been made strongly. However, there is still a distinct lack of formal support and supervision for career practitioners in the UK and elsewhere. This paper begins by defining support and supervision in the helping professions. It goes on to report the findings of a research project undertaken with a group of supervisors working in the context of 'youth support' and considers how the results might be applied to the career counselling profession. The hope is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…I believe clients' safety is essential in the therapeutic process. When clients feel safe in therapy, they are better positioned to advocate for their needs and feel empowered (Westergaard, 2013;Yotsidi et al, 2019). Studies support the conclusion of the importance of training, relevant education, and supervision in the building of safety, especially in northern, remote, and rural BC (Nutt & Sharpe, 2007).…”
Section: Fostering Clients' Safety In the Clinical Social Work Contextmentioning
confidence: 91%
See 1 more Smart Citation
“…I believe clients' safety is essential in the therapeutic process. When clients feel safe in therapy, they are better positioned to advocate for their needs and feel empowered (Westergaard, 2013;Yotsidi et al, 2019). Studies support the conclusion of the importance of training, relevant education, and supervision in the building of safety, especially in northern, remote, and rural BC (Nutt & Sharpe, 2007).…”
Section: Fostering Clients' Safety In the Clinical Social Work Contextmentioning
confidence: 91%
“…As a counsellor, I believe it is vital to mirror safety by being predictable; studies show that clients do not feel safe when the counsellor is unpredictable (Blanchard & Farber, 2016). Also, I believe receiving supervision and feedback is essential to improving clinicians' knowledge about engaging with clients purposefully and creating safety (Many et al, 2016;Westergaard, 2013). Northern, remote, and rural areas have distinct features that practitioners need to take into context in their practices (Collier, 2006;Graham et al, 2008).…”
Section: Fostering Clients' Safety In the Clinical Social Work Contextmentioning
confidence: 99%
“…These issues would be further exacerbated in situations where supervisors have dual roles as supervisor and worker. Westergaard (2013) found that supervisors and supervisees expressed how crucial it is for supervisees to have a safe space where they can talk about practice, process their experiences, and avoid internalizing experiences that come with working with vulnerable and difficult families. The research indicated that both supervisors and supervisees recognize the importance of supervision.…”
Section: Barriers To Supervisionmentioning
confidence: 99%